Administrative Procedure for Making an Airport Pass at The Manado Region VIII Airport Authority Office - Mandulangi, Jufrina; Silaban, Suri Yanti (Universitas Diponegoro, 2024)
The Manado Regional VIII Regional Airport Authority Office is a government agency that has the task of carrying out the regulation, control and supervision of flight activities at airports, one of which is service in the administration of making airport PAS (Public Address System). PAS services at airports are public services with the largest number of user services at the Airport. This is because many people other than passengers who will carry out activities in the limited security area of the airport must have an airport pass. Feedback submitted by service needs to be responded to and repaired so that the quality of services and procedures can be improved. Satisfaction of service users can be used as a benchmark to see an increase in service quality. The purpose of this study is to find out how the procedure for making airport passes. Descriptive research methods through literature study observation interviesws by collecting and collecting data from previous researchers, relevant articles and journals as well as data analysis methods, namely by describing, describing, and summarizing the results of data collection. The results of this observation indicate that services in making airport passes have a very important role in improving security in limited airport areas.